Revista oficial del Poder Judicial - Peru. Corte Suprema; Peru. Poder Judicial (República del Perú, Poder Judicial, 2007)
Devoted to research and scholarship in legal issues, administration of justice, technical reports, agreements or declarations of institutional congresses, as well as other relevant documentation on legal matters.
Keywords: Law : Peru : Periodicals; Law : Periodicals; Justice, Administration of : Peru : Periodicals; Electronic journals; Law; Justice, Administration of; Constitutional courts; Indigenous peoples : Legal status, laws, etc; Peru